Malting Barley Grain Quality in the Czech Republic, Crop 2016 - Ivo Hartman (Kvasný průmysl, 2017)
Quality parameters were assessed in 251 samples of malting barley from crop 2016 according to the standard ČSN 46 1100-5. Average contents of nitrogenous substances and starch were 11.6 % and 63.9 %, respectively. Sieving fractions above 2.5 mm achieved the average value of 92.0 %. Compared to crop 2015, a higher occurrence of physiologically, biologically and thermally damaged grains and grains with black tips was found. The occurrence of visible and hidden sprouting and with this defect associated loss of germinating capacity of grain during storage represents the highest risk for crop 2016.